Cross-Country Report on Spillovers : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2016)
This paper identifies policies to increase productivity in the East, reduce regional income disparities, and promote overall income convergence. Achieving this objective will require improving educational attainment and reducing skill mismatches in the East, scaling up public infrastructure to attract investment to less productive regions, and facilitating labor mobility. This paper also discusses female labor participation in Poland and the potential impact on bank profitability of the recently implemented bank asset tax. Poland's population is aging, yet it has an important underused source of qualified labor-its women. For Poland to unleash its full economic potential, it needs to embrace the vital contribution that women can make to its economy.